The social network in response to crisis in atempeted suicide: essencial links of attention - Silva, Maria de Nazareth Rodrigues Malcher de O; Izidio da, Ileno (Tempus – Actas de Saúde Coletiva, 2011)
This article presents some reflection of the importance of social network in crisis intervention of a person who attempts suicide, as one aspect of support in attention. The significant role of the network can serve assupport to deal with the individual who suffers and experiences a suicide attempt, and social networking service on the Public Policy of the Federal District, Brasília/DF, should follow a focused attention not only to the symptoms and consequences the act of suicide, but the care of the person suffering and their survivors. The circuit psychiatric serving these subjects is a blind alley, and only ad hoc, focusing on priority medical care. This circuit only helps take care of the suicidal act itself, and its associated symptoms. And as a result has multifactor forget the suicidal act, and care of survivors. Worse, causes psychiatrization to the person who commits an act of suicide and admissions with little investment in this context, turning him into a career of stigmatization.